2020
DOI: 10.1073/pnas.2012197117
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol 25-hydroxylase suppresses SARS-CoV-2 replication by blocking membrane fusion

Abstract: Cholesterol 25-hydroxylase (CH25H) is an interferon (IFN)-stimulated gene that shows broad antiviral activities against a wide range of enveloped viruses. Here, using an IFN-stimulated gene screen against vesicular stomatitis virus (VSV)-SARS-CoV and VSV-SARS-CoV-2 chimeric viruses, we identified CH25H and its enzymatic product 25-hydroxycholesterol (25HC) as potent inhibitors of SARS-CoV-2 replication. Internalized 25HC accumulates in the late endosomes and potentially restricts SARS-CoV-2 spike protein catal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
233
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(241 citation statements)
references
References 80 publications
(96 reference statements)
7
233
1
Order By: Relevance
“…IFITMs inhibit SARS‐CoV, 229E, and MERS‐CoV entry, but promote infection by HCoV‐OC43, a coronavirus that causes the common cold (Huang et al , 2011; Bertram et al , 2013; Warren et al , 2014; Wrensch et al , 2014; Zhao et al , 2014; Zhao et al , 2018). IFITMs, as well as other ISGs, including LY6E and Cholesterol 25‐hydrolase (CH25H), impair SARS‐CoV‐2 replication by blocking the fusion of virions (Pfaender et al , 2020; preprint: Zang et al , 2020; Zhao et al , 2020). Most of the experiments regarding these ISGs have been performed with single‐cycle viral pseudotypes.…”
Section: Introductionmentioning
confidence: 99%
“…IFITMs inhibit SARS‐CoV, 229E, and MERS‐CoV entry, but promote infection by HCoV‐OC43, a coronavirus that causes the common cold (Huang et al , 2011; Bertram et al , 2013; Warren et al , 2014; Wrensch et al , 2014; Zhao et al , 2014; Zhao et al , 2018). IFITMs, as well as other ISGs, including LY6E and Cholesterol 25‐hydrolase (CH25H), impair SARS‐CoV‐2 replication by blocking the fusion of virions (Pfaender et al , 2020; preprint: Zang et al , 2020; Zhao et al , 2020). Most of the experiments regarding these ISGs have been performed with single‐cycle viral pseudotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Viral entry was inhibited by 25HC in lung epithelial cells and organoids, via mechanisms requiring activation of acyl-CoA:cholesterol acyltransferase (ACAT), thereby promoting cholesterol transport from the cell membrane to the endoplasmic reticulum ( Wang et al., 2020c ). Consistent with these findings, Zang and colleagues used gain- and loss-of-function experiments to demonstrate key roles for interferon-stimulated CH25H and 25HC in the inhibition of viral membrane fusion and SARS-CoV-2 replication ( Zang et al., 2020 ).…”
Section: Intracellular and Extracellular Cholesterol Lipids And Stamentioning
confidence: 88%
“…Consistent with this possibility, one study showed that 27-hydroxycholesterol (27OHC) exerted SARS-CoV-2 antiviral activity in VeroE6 cells at 10 μM, and that overall oxysterols were lower in patients with moderate and severe COVID-19 symptoms than in controls ( Marcello et al., 2020 ). Another study showed that 25OHC had potent SARS-CoV-2 antiviral activity at similar concentrations ( Zang et al., 2020 ). These findings are in strong agreement with work from multiple groups that has demonstrated that 25OHC is a potent inhibitor of many enveloped viruses ( Liu et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%